The English Children and Families Act 2014 - Bainham, Andrew; Gilmore, Stephen (Victoria University of Wellington Law Review, 2015)
Parts I and II of the Children and Families Act 2014 may appear to make little change to English child law, largely amending existing statutes with provisions of a procedural and evidential flavour. Yet, as this article explains, it is deeply ideological legislation with roots in the Narey Report on adoption and the Family Justice Review. The article examines the background to the legislation and shows how, in the private law, statutory language was used to convey an "official" message concerning the importance of both separating parents remaining "involved" in their children’s lives. This resulted in enactment of a presumption of parental involvement in court decision making, and a more neutral "child arrangements order", replacing the supposed polarising duality of "residence" and "contact" orders with little more than a change of terminology and the disadvantage of greater complexity. The ideology underpinning the public law provisions is to encourage adoption by speeding up the process, getting children through care proceedings as quickly as possible and into adoptive families. This thinking may appear to clash with recent jurisprudence of the higher courts which has emphasised that adoption is a "last resort" in child protection, and that significant human rights issues arise. The analysis highlights a key question, cutting across the public and private law provisions, namely whether the 2014 Act dilutes English law’s long-standing commitment to the paramountcy of child welfare.